Simulating Indonesia’s Sugar Supply Policy Using a Simultaneous Equation Model - Nur Amin; Jusniaty Jusniaty; Fitriani Fitriani (Institut Agama Islam Negeri Kerinci, 2026)
Purpose: This study aims to analyze and simulate the effects of sugarcane production, sugar recovery rate, and domestic sugar consumption on national sugar supply, as well as to evaluate the policy implications of an integrated sugar supply management framework in Indonesia to maintain a balance between production enhancement and consumption control. Design/Methodology/Approach: This study employs a quantitative approach with an econometric analysis design. Equations were estimated using the two-stage least squares (2SLS) method. The data used in this study consists of secondary data in the form of a 30 year time series covering the period 1992 to 2021. The analysis is conducted using a simultaneous equation model to capture the interrelationships among variables. The validated model is subsequently used to perform policy simulations under several scenarios. Findings: The simulation results indicate that domestic sugar consumption has the most significant impact on national sugar supply compared to increases in sugarcane production and sugar recovery rates. A combined scenario involving increased production and recovery rates accompanied by a reduction in domestic sugar consumption yields the most optimal outcome in reducing import dependency and maintaining domestic supply balance. Research Implications: An integrated policy framework encompassing the production, trade, and consumption sectors is required to strengthen the resilience of Indonesia’s sugar supply system amid global market fluctuations.